A brief analysis of hypocenter location accuracy and its influencing factors - Fengxue Zhang; Yu Li; Yiping Chen (地球与行星物理论评)
Earthquake location is fundamental to seismological research. However, there exists a supply contradiction between seismic location accuracy and the needs of seismological studies. Different studies require varying levels of accuracy in earthquake location. For example, studies on focal mechanisms and crust-mantle structures demand accuracy at the kilometer level, while industrial activities and induced seismicity researches require accuracy at the hundred-meter level. Yet, the accuracy of earthquake locations provided by seismic monitoring networks is only within a few kilometers. Numerous earthquake localization methods have been optimized and improved from different perspectives, but their focuses vary. Overall, existing localization methods have not paid sufficient attention to the accuracy of earthquake positioning. In extensive earthquake localization practices, predecessors have developed several empirical rules for optimizing earthquake position accuracy. These empirical rules not only vary by region but also have specific applicability conditions, and they still need further optimization and refinement. This paper briefly analyzes the various factors influencing the accuracy of earthquake localization and conducts targeted research. It has achieved some progress in earthquake localization algorithms and the quality control of observational data. The study supplements the coupling relationship in earthquake localization by exploring the constraints among the velocity model, hypocenter location, and origin time. Additionally, the paper proposes the use of a stepwise elimination process in the earthquake localization workflow.